2018
DOI: 10.1186/s12889-018-5431-8
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of government strategies for financial protection against costs of hospitalization Care in India

Abstract: BackgroundIn the past decade, India has seen the introduction of many ‘publicly funded health insurance’ schemes (PFHIs) that claim to cover approximately 300 million people and are essentially forms of purchasing care from both public and private providers to reduce out-of-pocket expenditure (OOPE) for hospitalization.MethodsData from a recent government-organized nationwide household survey, The National Sample Survey 71st Round, were used to analyse the effectiveness and equity of tax-funded public health s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
131
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 66 publications
(141 citation statements)
references
References 14 publications
10
131
0
Order By: Relevance
“…Publicly funded health insurance (PFHI) coverage and tax based subsidized public provisioning are the two major strategies used by the government for providing nancial risk protection in India [17].…”
Section: Financial Risk Protectionmentioning
confidence: 99%
See 1 more Smart Citation
“…Publicly funded health insurance (PFHI) coverage and tax based subsidized public provisioning are the two major strategies used by the government for providing nancial risk protection in India [17].…”
Section: Financial Risk Protectionmentioning
confidence: 99%
“…For CHE-10 and CHE-25, other than the above mentioned independent variables, choice of provider (public or private) was used. To understand factors affecting living arrangements and economic independence in the elderly population, chances of 'living alone', and chances of 'being dependent' were dependent variables, with same independent variables (except economic independence and living arrangments) mentioned above for the logit model hospitalization, These variables have been included based on suggestions from existing literature [11][12][13][14][15][16] . No multicollinearity was found among independent variables.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, most of the recently launched government insurance schemes started with the promise of cashless hospitalized care for those below poverty line and unorganized workers, do not show any impact on reduction of financial hardships. Other studies have also shown this limitation of insurance sector in assisting financial protection of patients with all health conditions . The strategy for financial protection has to depend largely on public provisioning; but re‐examining the package of services in insurance schemes and better monitoring as well as regulation of private health care providers may help insurance programs improve access and financial protection by utilising the relatively economic and ethical private health care providers.…”
Section: Discussionmentioning
confidence: 99%
“…Out of pocket expenditure for hospitalization was calculated by subtracting reimbursements by insurance companies and other sources from the total medical expenditure and transportation cost. However, across India only 2% of hospitalisations had reimbursements in the preceding 1 year …”
Section: Methodsmentioning
confidence: 99%
“…Lower enrolments have been found in remote rural areas, poorer districts, socio-economically vulnerable groups, indigenous communities and female-headed households [34–36]. A few studies of utilization of hospital care under state-funded health insurance in India have found inequities based on caste, economic status, education and urban–rural residence [3638]. …”
Section: Introductionmentioning
confidence: 99%